(Sub)alternative Muslim Perceptions of Law and Justice: Beyond Politics of Fiqh and Inadequacy of Human Rights Discourse - Hamzić, Vanja (2011)
This paper comparatively examines some present-day perceptions of the concepts of law and justice by sexually- and/or gender-variant Muslim communities, living in Muslim-majority states. Firstly, it analyses their encounters with two hegemonic identitarian/ideological discourses: that of Muslim theopolitical reductionism and that of the exclusionary neoliberal homonormative identity politics. Secondly, the paper discusses the strategies devised to resist these hegemonic currents and to negotiate the communities’ own takes on law (including both on Islamic legal tradition and on international human rights law) and justice (including concepts such as social and gender justice). Thirdly, it is argued that concepts of law and justice, as re-claimed and re-developed by sexually - and/or gender-variant Muslim communities – notwithstanding their respective national, cultural and religious specificities – not only challenge the two identified hegemonic discourses, but also test the limits of global movements/disciplines developed, inter alia, as the critical alternatives to those two oppressive identitarian ideologies. Those include queer theory, in its capacity (or the lack thereof) to represent or research the communities whose intrinsic ties transcend the sexuality/gender scripts, and the dominant human rights discourse, in its reliance on rigid legalism inapt to accommodate more nuanced social justice claims.